If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1f = -2f + 3 Reorder the terms: -1f = 3 + -2f Solving -1f = 3 + -2f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '2f' to each side of the equation. -1f + 2f = 3 + -2f + 2f Combine like terms: -1f + 2f = 1f 1f = 3 + -2f + 2f Combine like terms: -2f + 2f = 0 1f = 3 + 0 1f = 3 Divide each side by '1'. f = 3 Simplifying f = 3
| 4x^3+12x^2+12x^2-3=o | | 20+6(2x+4)192= | | 136/9:8 | | 8+2t=32 | | 9+4y=6+7y | | -10v^2=160 | | -3s=-4s-7 | | -(x+6)-31(x+4)=-162 | | 3+5d=4d+6 | | -[3-3x-30+5x]-14= | | 95X+71Y=46 | | 4x-6=6x-13 | | 7-7(-6m+5)=308 | | 8/35-2/15= | | 4q+10=3q | | 10(x-7)=-50+12x | | 4/x^2-12=1 | | -5=-10g+5 | | 50+15h=140 | | 4*12=75 | | 4*5=75 | | 9p+7=8p | | 7-2x=7x+7 | | w+4.68=9.25 | | 3y-2+3y-2= | | -9+8c=5c | | 17+445= | | -2h=-h+9 | | 12t+12t=-24 | | 1+8x=-11-4x | | 7y=21+5x | | 5(x+.40)=5 |